Analisis Prinsip Keadilan dan Kepastian Hukum Perkara Warisan (Studi Putusan No.40/Pdt.G/2024/PTA.Mks) - Mulyadi, Andi Muh. Rizqi; Darmawangsa, Andi; Mallongi, Maryati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study is a normative legal research using a qualitative approach, which applies statutory, case, and conceptual approaches to analyze the principles of justice and legal certainty in an Islamic inheritance dispute. The research focuses on the appellate decision of the Makassar Religious High Court No. 40/Pdt.G/2024/PTA.Mks. Data were collected through document analysis (court rulings, legal norms, and doctrines) and interviews, and then examined qualitatively and descriptively.The findings reveal that the first-instance decision was merely declarative and did not fulfill the principle of legal certainty, as it lacked an executable operative ruling. In contrast, the appellate decision clarified each heir’s share and explicitly ordered the division of inheritance, thus upholding the principles of lex certa and lex executoria. In terms of justice, the decision of the PTA Makassar serves as a corrective to the unilateral domination of the estate and aligns with the Islamic legal theories of maqāṣid al-sharī‘ah (Al-Ghazali), hikmah and ‘illat (Al-Syatibi), qath‘iyyat al-dalālah (Imam Syafi’i), and divine justice (al-‘adl al-ilāhī, Ibn Taymiyyah). The study also compares the case with the Supreme Court Decision No. 845 K/Pdt/2024 to assess jurisprudential consistency in resolving inheritance disputes in the religious court system. The appellate decision is found to embody substantive justice and enforceable legal certainty effectively and fairly.